DC Stark addressing for quantum memory in Tm:YAG - Gerasimov Konstantin; Minnegaliev Mansur; Urmancheev Ravil; Moiseev Sergey (EPJ Web of Conferences, 2017)
We observed a linear DC Stark effect for 3H6 – 3H4 optical transition of Tm3+ ions in Y3Al5O12. We observed that application of electric field pulse suppresses the two-pulse photon echo signal. If we then apply a second electric pulse of opposite polarity the echo signal is restored again, which indicates the linear nature of the observed effect. The effect is present despite the D2 symmetry of the Tm3+ sites that prohibits a linear Stark effect. Experimental data analysis shows that the observed electric field influence can be attributed to defects that break the local crystal field symmetry near Tm3+ ions. Using this effect we demonstrate selective retrieval of light pulses in two-pulse photon echo.